Efisiensi Produksi Kelapa Sawit Pola Swadaya Di Desa Senama Nenek Kec Tapunng Hulu Kabupaten Kampar - Zulhamid Ridho; Syaiful Hadi; Jumatri Yusri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aims to how level for the factors of production in non former-farmers in the Senama Nenek village from the aspects of technical efficiency, allocative efficiency and economic efficiency. The samples were calculated using purposive sampling is done by taking as many as 40 non former-farmers. Data were analyzed using two functions, the Cobb-Douglas production function and frontier Cobb-Douglas. Cobb-Douglas used see whether there is the classical assumptions. Cobb-Douglas stochastic frontier as an approach based on the consideration for the measurement of technical efficiency, allocative and economical by using the approach in terms of input and output are integrated. Factors affecting the production of palm oil by the method of Maximum Likelihood Estimation (MLE) is urea, KCl, SP36, and Dolomite. Factors affecting the level of palm oil production inefficiencies are aged farmer, aged Palm Oil. Oil palm plantation businesses are efficient in the use of a combination of factors of production, but not allocative efficient, and economical. Keywords: Technical , allocative, Economic